The efficacy and the immunomodulatory effect of rifaximin in prophylaxis of spontaneous bacterial peritonitis in cirrhotic Egyptian patients - Mostafa, Tarek; Badra, Gamal; Abdallah, Mahmoud (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: This study aimed to evaluate the efficacy and the immunomodulatory effect of rifaximin as another promising prophylactic therapy against spontaneous bacterial peritonitis (SBP) in cirrhotics. Materials and Methods: Seventy cirrhotic patients with ascites were included in the study. Patients were divided into two groups in a randomized single-blind fashion. Group one (n=40) received rifaximin and group two (n=30) received norfloxacin (control group). The treatment duration was 6 months. Serum levels of tumor necrosis factor alpha (TNF-α), interleukin-6 ( IL-6), and interleukin-10 (IL-10) were the primary inflammatory markers of the study to evaluate the effect of the medications used. Results: Three months after treatment, five cases on norfloxacin therapy showed SBP, whereas all cases on rifaxmine therapy were free from SBP. In addition, there was no significant difference between patients on rifaximin and norfloxacin therapy with respect to TNF-α, IL-6, and IL-10 serum levels (p>0.05). Furthermore, patients on both rifaximin and norfloxacin therapies showed a statistically significant decrease in TNF-α and IL-6 serum levels compared with their baseline levels (p=0.000 and p=0.000, respectively). In contrast, serum IL-10 showed a statistically significant increase in both groups in comparison with its baseline level (p>0.00). Six-month after treatment, patients on rifaximin therapy showed more effective remission from SBP than those on norfloxacin therapy. Conclusion: In conclusion, the use of rifaximin not only prevents bacterial translocation but also modulates the immune response of the inflammatory and the anti-inflammatory cytokines in SBP patients. However, the efficacy and the immunomodulatory effect of rifaximin in the prophylaxis of SBP in cirrhotics needs further prospective large-scale, double-blind studies.